JavaScript programmer's reference - Reid, Jonathan; Valentine, Thomas (Apress Imprint: Apress, 2013)
JavaScript Programmer's Reference is an invaluable resource that won't stray far from your desktop (or your tablet!). It contains detailed information on every JavaScript object and command, and combines that reference with practical examples showcasing how you can use those commands in the real world. Whether you're just checking the syntax of a method or you're starting out on the road to JavaScript mastery, the JavaScript Programmer's Reference will be an essential aid.  With a detailed and informative tutorial section giving you the ins and outs of programming with JavaScript and the DOM followed by a command-by-command reference, your next project will pop with interactivity and keep your audience coming back for more. JavaScript Programmer's Reference is your one-stop source for everything you'll need to know to become a cutting edge web developer using the latest tools and techniques available today.    In depth explanations and activities to explain not just the command in question, but why it is used in that way Progressive learning curve to not overwhelm and confuse you Handy and extremely informative quick-reference of every command within the JavaScript & DOM specifications